PENGARUH PERBEDAAN JENIS WARNA CAHAYA LAMPU DAN KEPADATAN KANDANG TERHADAP PERFORMANCE PADA PEMBESARAN BURUNG PUYUH (Coturnix coturnix japonica) JANTAN - Efi Rokhana; Waryani - (Jurnal Ilmiah Fillia Cendekia, 2016)
Quail performances was caused by several reasons such as light color and cage density. The purpose of this research was to find the influence of light color and cage density to male quail performances during 5 weeks fattening. Method was used in this reseach was Completely Randomized Design with factorial pattern containing two factors were light color (white, yellow, green) and cage density (40 male quail/ m2 and 60 male quail/ m2). The measured variable were feed intake, body weight gain and feed conversion rate. The result showed that the varieties of light color and cage density on male quail give no effect (P> 0.05) on feed intake, body weight gain and feed conversion rate for 5 weeks fattening period.